2018
DOI: 10.1002/brb3.959
|View full text |Cite
|
Sign up to set email alerts
|

An overview of protective strategies against ischemia/reperfusion injury: The role of hyperbaric oxygen preconditioning

Abstract: IntroductionIschemia/reperfusion (I/R) injury, such as myocardial infarction, stroke, and peripheral vascular disease, has been recognized as the most frequent causes of devastating disorders and death currently. Protective effect of various preconditioning stimuli, including hyperbaric oxygen (HBO), has been proposed in the management of I/R.MethodsIn this study, we searched and reviewed up‐to‐date published papers to explore the pathophysiology of I/R injury and to understand the mechanisms underlying the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 156 publications
(220 reference statements)
0
69
0
4
Order By: Relevance
“…Besides being carried through by blood, oxygen reaches to the cellular level also by diffusion from the interstitial tissue in which it reaches high concentration during HBO treatment. It improves endothelial function and decreases local inflammation and edema [14]. Also, as increased ROS is associated with enhanced RVR, we can assume that upregulated antioxidant enzyme activities [40,41] after HBO preconditioning may decreased RVR by ROS scavenging that would further improve renal hemodynamic.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Besides being carried through by blood, oxygen reaches to the cellular level also by diffusion from the interstitial tissue in which it reaches high concentration during HBO treatment. It improves endothelial function and decreases local inflammation and edema [14]. Also, as increased ROS is associated with enhanced RVR, we can assume that upregulated antioxidant enzyme activities [40,41] after HBO preconditioning may decreased RVR by ROS scavenging that would further improve renal hemodynamic.…”
Section: Discussionmentioning
confidence: 96%
“…HBO is used to increase blood oxygen level that can penetrate to ischemic areas and perilesioned tissue more deeply than under normobaric conditions and has found its place, as primary or adjuvant therapy in the treatment protocols for different clinical conditions [11][12][13]. Experimental studies and clinical observations support the evidence that HBO preconditioning has beneficial effect in postischemic reperfusion injury [12][13][14]. It improves oxygen delivery to an area with diminished circulation, resulting in improved endothelial function and decreased local inflammation and edema.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…65,66 Consequently, defining the molecular mechanisms underlying the I/R injury can improve the success of reperfusion treatment and enhance the clinical advantages for patients with stroke. 67 Numerous biological processes involving calcium excess, oxidative stress, inflammatory reactions, and endoplasmic reticulum stress are closely related to the brain I/R injury. 65,68 Interestingly, each of these activities can be influenced by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…HBO which is beneficial for formation of new blood vessels and repairing the function of nerve tissue is a noninvasive treatment for I/R disease [14]. Some researchers have reported that preconditioning HBO can protect against nervous I/R injury [15].…”
Section: Introductionmentioning
confidence: 99%